Water‐resistant conductive organogels with sensation and actuation functions for artificial neuro‐sensory muscular systems. Issue 4 (13th April 2022) - Zhang, Zhixing; Yu, Yunfei; Yu, Huitao; Feng, Yiyu; Feng, Wei
Abstract: The development of functional flexible conductive materials can significantly contribute to the improvement of intelligent human–computer integration. However, it is a challenge to endow human–machine interface with perception and response actuation simultaneously. Herein, a customizable and multifunctional electronic conductive organogel is proposed by combining conductive carbon nanotube (CNT) clusters and flexible adhesive organogels. The conductive CNT cluster layers generated on the surface of organogels equip the resulting organogel‐based conductors with considerable quasi‐superhydrophobicity and increase their potential applicability as highly sensitive stress and strain sensors. In particular, this quasi‐superhydrophobicity is insensitive to tensile strain. Based on customizable conductive networks and entropy‐driven organogel actuation, the conductive organogels can sense various strain and stress signals and imitate natural organisms with muscle actuation and neurofeedback. This strategy for preparing electronic conductors can enhance the rational design of soft robotics and artificial intelligence devices, facilitating further progress of human‐like intelligent systems. Abstract : Flexible water‐resistant conductive materials are developed by combining adhesive organogels and conductive carbon nanotube (CNT) clusters. A typical neuromuscular system with actuation, adhesion, and perception can be imitated by the customizable conductor based on the shape memory effect of organogels and the conductivity of CNT cluster layer. These multiple functions of resulting conductors can be widely applied in artificial intelligence.